The dehybridization of social enterprises - Plesa, M (2022)
In the world of hybrid organizations, an important and under-examined phenomenon is the process of transforming from a hybrid structure to an organizational form with fewer logics. This research introduces the concept of dehybridization, which I define as a process through which an organization transforms in a way that integrates fewer institutional logics than previously. To examine the phenomenon of dehybridization in the context of social enterprises, I draw on the hybridity and hybrid organizations literatures. These literatures are integral in gaining a conceptual understanding of the challenges of hybrids and their transformations. Building upon this theory, I propose a conceptual framework that describes how dehybridization occurs in hybrid organizations and empirically study this phenomenon in a three-paper dissertation. The first paper introduces and defines the concept of dehybridization and illustrates the potential process for hybrid organizations. The second paper draws on a dataset of 33,350 Community Interest Companies in the United Kingdom from 2006-2020 to examine the relationship between organizational governance and dehybridization. The third paper draws on the same dataset and examines how three exogenous shocks (2007-2008 Financial Crisis, Brexit Vote, and Covid-19 Lockdown) affected the management of hybrid tensions in social enterprises.